Influence of genetic counselor medical history on specialty and psychosocial practice in North America. Issue 3 (26th November 2021) - Amos, Kaitlyn; McCarthy Veach, Patricia; Wagner, Chelsea; Czerwinski, Jennifer; Murphy, Lauren; Mork, Maureen; Singletary, Claire N.
Abstract: A personal or family medical history is inherently part of a genetic counselor's life story. Yet, the degree to which this history influences counselors' clinical specialty choice and professional psychosocial practice is unexplored. A medical diagnosis may foster capacity for greater empathy, understanding, and rapport‐building self‐disclosure. Conversely, it could lead to disruptive countertransference, compassion fatigue, and eventually burnout. Research, however, has not specifically investigated this intersection. The aim of this study was to explore the impact of genetic counselors' personal and/or family medical history on choice of practice area and self‐perceived impact on their psychosocial work within sessions. Members of the National Society of Genetic Counselors were recruited to complete an online screening survey. Of the 69 survey respondents that met inclusion criteria, 23 volunteered for and completed a telephone interview. Interview questions explored counselors' medical narratives and their consequent influence on specialty choice and clinical interaction with patients. Inductive analysis yielded nine domains within three major themes: Medical Story, Specialty Impact, and Psychosocial Influence. Participants were more likely to be attracted to a specialty possessing overlap with their medical history and attributed many of their psychosocial strengths to personal and/or family medical experiences, such as increased empathy or a more expansive scope in how they cared for patients. Many counselors, however, noted their medical history did not frequently influence their clinical practice, with most initially denying or downplaying use of self‐disclosure about their history. Contradictory to their statements, the majority gave at least one example of self‐disclosure, whether indirect, prompted, or direct. Importantly, almost all participants named or demonstrated countertransference. This study highlights that while medical history can be a valuable asset in providing care for patients, it requires a genetic counselor's diligent attentiveness and commitment to honest self‐reflection.